Indonesian EFL Learners' Motivation to Learn Second Language Pragmatics - Sanjaya, I Nyoman Suka; Wajdi, Majid; Sitawati, Anak Agung Raka; Suciani, Ni Ketut (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Despite the significance of motivation and pragmatic competence for L2 learners, surprisingly, research into L2 pragmatics learning motivation is almost non-existent. Drawing on the self-determination theory of human motivation, the present study was carried out to investigate the level and nature of Indonesian EFL learners’ motivation for L2 pragmatics learning. A total of 76 Indonesian-speaking sophomores studying international business management were asked to fill out a tailor-made, 29-item online questionnaire designed to measure the level and nature of their motivation for L2 pragmatics learning. It was found that (i) Indonesian EFL students’ motivation for L2 pragmatics learning was insufficiently high, (ii) their intrinsic motivation was the highest compared to other types of motivation, and (iii) their external motivation was surprisingly low. These findings can be explained in the light of the students’ previously instructed foreign language learning experiences which placed undue emphasis on the formal aspects of the target language while marginalizing the social ones. Pedagogically, the findings imply that, owing to the malleability of human motivation, EFL teachers should employ principled instructional methods to promote their students’ L2 pragmatics learning motivation. Be that as it may, further studies need to be conducted to (in) validate the above-mentioned findings, taking into consideration the limitations of the present study.